Photo-induced manipulation and relaxation dynamics of Weyl-semimetals - Jakub Šebesta; Oscar Grånäs (npj Computational Materials)
Abstract The use of ultrashort laser pulses to manipulate properties or investigate a materials response on femtosecond time-scales enables detailed tracking of charge, spin, and lattice degrees of freedom. When pushing the limits of experimental resolution, connection to theoretical modeling becomes increasingly important to infer causality relations. Weyl-semimetals are a particular class of materials of recent focus due to the topological protection of the Weyl-nodes, resulting in a number of fundamentally interesting phenomena. This work provides a first-principles framework based on time-dependent density-functional theory for tracking the distribution of Weyl-nodes in the Brillouin-zone following an excitation by a laser pulse. Investigating the prototype material TaAs, we show that residual shifts in the Weyl-Nodes’ position and energy distribution are induced by a photo-excitation within femto-seconds through band-structure renormalization. Further, we provide an analysis of the relaxation pathway of the photoexcited band-structure through lattice vibrations.